2014
DOI: 10.1002/hec.3069
|View full text |Cite
|
Sign up to set email alerts
|

Payment Mechanisms and the Composition of Physician Practices: Balancing Cost‐Containment, Access, and Quality of Care

Abstract: We take explicit account of the way in which the supply of physicians and patients in the economy affects the design of physician remuneration schemes, highlighting the three-way trade-off between quality of care, access, and cost. Both physicians and patients are heterogeneous. Physicians choose both the number of patients and the quality of care to provide to their patients. When determining physician payment rates, the principal must ensure access to care for all patients. When physicians can adjust the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Several theoretical papers argue that the more altruistic physicians should be paid on a capitated basis (e.g., Eggleston, ; Jack, ) regardless of the patient's severity of illness. Barham and Milliken () show, however, that high‐severity patients should be treated by physicians paid by FFS, whereas the least altruistic physicians treating healthy patients should be paid by CAP. Our behavioral results demonstrate that mixed payment systems—if designed such that tradeoffs between profit maximization and rendering the optimal benefit to the patient are reduced—might help to incentivize less altruistic physicians to choose patient‐optimal care for both low‐severity and high‐severity patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several theoretical papers argue that the more altruistic physicians should be paid on a capitated basis (e.g., Eggleston, ; Jack, ) regardless of the patient's severity of illness. Barham and Milliken () show, however, that high‐severity patients should be treated by physicians paid by FFS, whereas the least altruistic physicians treating healthy patients should be paid by CAP. Our behavioral results demonstrate that mixed payment systems—if designed such that tradeoffs between profit maximization and rendering the optimal benefit to the patient are reduced—might help to incentivize less altruistic physicians to choose patient‐optimal care for both low‐severity and high‐severity patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our first research question addresses how physicians prioritise patients in a capitationbased system. According to the literature, high-need patients suffer the greatest loss of care under this payment scheme (Barham and Milliken 2015;Brosig-Koch et al 2015;Ellis 1998;Hennig-Schmidt, Selten, and Wiesen 2011). Nonetheless, it has not yet been studied thoroughly how resource constraints affect care provision of high-need patients under capitation.…”
Section: Research Questionsmentioning
confidence: 99%
“…The drawback of capitation-based payment schemes is that it forces physicians to make a trade-off between own income and patient benefits thereby incentivising them to provide less than the patient-optimal amount of care (Barham and Milliken 2015;Brosig-Koch et al 2015;Ellis 1998;Ellis and McGuire 1986;Hennig-Schmidt, Selten, and Wiesen 2011). The literature has shown that it is the high-need patients who suffer the greatest loss of care from this trade-off (Barham and Milliken 2015;Brosig-Koch et al 2015;Ellis 1998;Hennig-Schmidt, Selten, and Wiesen 2011), implying that capitation potentially leads to an inequitable distribution of health care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Chalkley and Listl (2018) who study remuneration's impact on the incidence of X-rays in dentistry, the imperative to balance clinical harms and benefits should not be influenced by payment models. The ordering of lab tests provides a well-defined context to assess the impacts of payment models on clinical practices that have no 1 For example, Barham and Milliken (2015), Barros (2003), Clemens and Gottlieb (2014), and Helmchen and Lo Sasso (2010). direct financial impact on physicians but may be redundant/costly and potentially produce biased evidence regarding patient health.…”
Section: Introductionmentioning
confidence: 99%